Audit Outsourced Data in Internet of Things. (8th May 2021) - Hou, Gaopan; Ma, Jianfeng; Li, Jiayi; Liang, Chen
Abstract : With the increase in network transmission rates, the Internet of Things (IoT) has gradually become a trend. Users can upload the data generated by the device to the cloud database to save local storage space, thereby reducing local storage costs. Because uploading data to the cloud loses physical control of the data, an audit is required. Traditional audit protocols are not completely suitable for lightweight devices in the IoT. This paper proposes a new type of audit protocol suitable for lightweight devices with weak computing power. This protocol transfers part of the computation of data tags to a cloud storage provider (CSP) with strong computing power, thereby reducing the introduction of computing entities. Our scheme supports the dynamic operation of data and guarantees the effectiveness of challenge response by blockchain. Compared with existing schemes, our scheme is more secure and effective.